PENGARUH MOTIVASI, KOMPENSASI, DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BALAI KONSERVASI BOROBUDUR DI MASA PANDEMI - Wahidah, Naela Lailatul; Verawati, Dian Marlina (Transpublika Publisher, 2022)
This research was conducted to determine the effect of motivation, compensation and work environment on work productivity of Borobudur Conservation Center employees during the pandemik. This research is a quantitative research with a sampling technique in the form of purposive sampling, where the researcher takes a number of respondents who are used as samples with certain criteria and considerations so that 34 respondents are obtained as (PNS) from the population which includes all employees of the Borobudur Conservation Center as many as 100 people. In the data analysis test, the author uses multiple linear regression testing and hypothesis testing using the SPSS 25.0 for windows program. The results of the analysis were obtained based on the t test (partial) the results obtained if partially the motivational variable had no effect on work productivity, while the compensation variable and work environment variables had a partial effect on work productivity. For the results of the F test, the variables of motivation, compensation and work environment simultaneously affect the work productivity of Borobudur Conservation Center employees with a significant value of 0.000 < 0.05 and also obtained a value of Fcount 25.159 > Ftable 2.91.